Biomass of Chlorella sp. As green corrosion inhibitor for mild steel / Adam Harris Roslan - Roslan, Adam Harris (2023)
Corrosion is a huge and ongoing issue that causes substantial problems for the environment, our assets, and our lives, as well as economic losses especially in the industries. As a result, corrosion prevention requires additional focus. Metal corrosion inhibitors, both inorganic and synthetic, are used to prevent and slow corrosion, but they are dangerous. Green corrosion inhibitors, which are both environmentally and economically friendly, are so likely to provide the solution to this problem. In this paper, the biomass of the unicellular green algae Chlorella sp., which synthesises a high quantity of protein, was investigated as a natural inhibitor of mild steel corrosion in 0.2 mol L-1 H2SO4 by Fourier-transform infrared spectroscopy (FTIR) analysis and gravimetric analysis to determine Inhibition Efficiency (IE%), Corrosion Rate (CR), and Surface Coverage (Ø). Furthermore, the thermodynamic characteristics of the adsorption process, such as Activation Energy (Ea), Enthalpy (H°), and Entropy (S°), were determined, and the results demonstrated a favourable interaction.